Problems of Consideration of Individual Labor Disputes of Athletes and Coaches in the Jurisdictional Bodies of Sports Federations and Professional Sports Leagues - Ya. N. Rzhepik (Теоретическая и прикладная юриспруденция)
The article is devoted to the problems of consideration of individual labor disputes of athletes and coaches in the jurisdictional bodies of sports federations and professional sports leagues. The current legislation provides for the possibility of creating bodies of pre-trial settlement of disputes in the ﬁeld of physical culture and sports within the structure of all-Russian sports federations and professional leagues, which can consider individual labor disputes of athletes and coaches. At the same time, certain problems arise already at the stage of determining the jurisdiction of these bodies in terms of the possibility of considering individual labor disputes by them. Within the framework of this study, the problems related to the issues of the correlation of labor legislation and legislation on physical culture and sports, related to the procedure and conditions for the formation of jurisdictional bodies, the peculiarities of submitting a dispute for their consideration, and the observance of the principle of equality of the parties are identiﬁed. Proposals have been developed to improve the current legislation.